Survey on Smart City Platform Development through Waste Management - Sindhuja, S.; Suresh Kumar, M.; Padmavathy, R.; Bagya Lakshmi, K. (Asian Journal of Science and Applied Technology, 2018)
The global challenge of ensuring smart city in growing cities has inspired on implementing solid waste management. Clean and pure environment helps people to lead a healthy life. It is becoming a critical issue due to rapid increase in population. Appropriate solid waste management systems are important for improving the environment and the well-being of residents.In the Present Scenario we have seen that there are different waste boxes and over-weight trash cans in the urban gatherings and the area territories that are flooding an immediate aftereffect of wealth waste. Now it is very necessary to create an Internet of Things (IoT) based waste management structure to make our city clean and neat. This paper is a survey on all possible way to implement solid waste management.